Pengaruh Environmental, Social, and Governance terhadap Nilai Perusahaan pada Perusahaan Subsektor Food & Beverage - Logas Logas; Syarif M. Helmi; Djunita Permata Indah (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) on firm value in Food & Beverage subsector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. This study employed a quantitative approach using secondary data obtained from annual reports, sustainability reports, and the companies' official websites. The sample consisted of 80 observations selected using the purposive sampling method. Firm value was measured using Tobin’s Q, while ESG was measured using the ESG disclosure score. Multiple linear regression analysis was conducted using SPSS. The results indicate that ESG has no significant effect on firm value (? = 0.217; Sig. = 0.473). The control variables, Firm Size and Debt to Equity Ratio (DER), also have no significant effect on firm value. Simultaneously, ESG, Firm Size, and DER do not significantly affect firm value (Sig. = 0.249), with an Adjusted R Square value of 0.015, indicating that the model explains only 1.5% of the variation in firm value, while the remaining variation is explained by other factors outside the research model. This study contributes empirical evidence on the relevance of ESG disclosure to firm value in the Food & Beverage subsector while controlling for Firm Size and Debt to Equity Ratio (DER), thereby extending ESG literature in the Indonesian corporate context.